Aplikasi Absensi Berbasis Android Pada Sekolah Boarding Sebagai Transformasi Digital Bidang Pendidikan - Ahya Radiatul Kamila; Gerry Hudera Derhass; Deswin Auliyaa Rabbani; Johanes Fernandes Andry; Francka Sakti Lee (NUANSA INFORMATIKA, 2024)
Boarding schools require students and staff to reside on campus for a set period, necessitating high levels of security and comfort to optimize educational outcomes through effective human resource management. Managing staff and student attendance is crucial in these settings, exemplified by the manual attendance system at Insan Cendikia Magnet School in Bogor. However, manual systems often suffer from inefficiencies, inaccuracies leading to data errors, fraud, and real-time monitoring challenges. To address these issues, this study developed a digital attendance system using FlutterFlow, employing barcode scanning for both academic and non-academic staff. Implementation of this system improved digital attendance processes, with testing confirming its reliable performance. The system effectively met user needs and conditions, integrating attendance data with real-time reporting features. These accessible reports facilitate evaluation and decision-making regarding staff attendance.